REDUCTION OF NUTRIENT STATUS NASOPHARYNGEAL CANCER PATIENTS AFTER RADIOTHERAPY WITH COBALT - 60 IN SANGLAH HOSPITAL - Sudiasa, Putu; Tjekeg, Made; Puteri, AA Sagung Puteri (Medicina, 2012)
Nowadays radioterapy is still a standard treatment for nasopharyngeal cancer. Treatment with radiotherapy and or chemotherapy can effect the nutrient status of patients. Body Mass Index ( BMI ) is an indicator of a nutrient status measurement. BMI is expressed as body weight in kilograms divided by height squared in meters size. The objective of this study is to define the alteration of nutrient status in nasopharyngeal cancer patients with who underwent radiotherapy with Cobalt -60. With pre-post test single group method. The result showed significant decrease (P<0,05) of body weight a[er radiotherapy, i.e from 59.01 (SD 14.30) kg to 52.51 (SD 14.24) kg. Body mass index (BMI) prior to radiotherapy 22.42 ( SD 4.35 ) kg/m2 and a[er radiotherapy 19.89 ( SD 4,23) kg/m2. It was concluded that there is a significant nutrient status reduction in nasopharyngeal cancer patients a[er radiotherapy with Cobalt-60